Analisis Morfosemantik terhadap Fi’il Mazid dalam Al-Qur’an Juz I - Rona Handayani; Wiwit Yusnida Ritonga; Rahmayani; Afrahul Fadilah; Rosita Dongoran (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Morphosemantic Analysis of the Fi'il Mazid in the Qur'an in one Juz, focusing on the word structure, meaning, and context, involves a linguistic approach to examine the morphological structure and meaning of these words in the context of the Qur'an. The analysis of Fi'il Mazid's morphosemantics in the Qur'an in one Juz provides deep insights into the role and significance of Fi'il Mazid in conveying theological and moral messages in the Qur'anic text. The implications of this research can help enrich understanding of the language of the Qur'an and its application in everyday life.